The energy and effect of ionization on cluster formation and post ionization dynamics of energetic materials : a density functional study on (C3H6N6O6)2 - Kıyak, Güven. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
In this work, structures and energetics of (C3H6N6O6)2 and [(C3H6N6O6)2]+ molecules have been investigated via computational chemistry methods. Using Density Functional Theory, the neutral and positively charged dimer structures of C3H6N6O6 have been calculated. The adiabatic and vertical ionization energies have been bracketed between 8 and 10 eV. The dominant dissociation pathways have been identified. Possibilities for further clustering have been investigated. A sum of 33 neutrals and 27 cations have been found. These structures coexist within an energy range of 30 kJ/mol. Cations are encountered in the form of charge-dipole complexes and proton-transfer complexes while the neutrals are brought together by long range dispersion forces.
Keywords: Ionization.